Different Trichoscopic Features of Tinea Capitis and Alopecia Areata in Pediatric Patients - Abd-Elaziz El-Taweel; Fatma El-Esawy; Osama Abdel-Salam (Dermatology Research and Practice)
Background. Diagnosis of patchy hair loss in pediatric patients is often a matter of considerable debate among dermatologists. Trichoscopy is a rapid and noninvasive tool to detect more details of patchy hair loss. Like clinical dermatology, trichoscopy works parallel to the skin surface and perpendicular to the histological plane; like the histopathology, it thus allows the viewing of structures not discovered by the naked eye. Objective. Aiming to compare the different trichoscopic features of tinea capitis and alopecia areata in pediatric patients. Patients and Methods. This study included 40 patients, 20 patients with tinea capitis and 20 patients with alopecia areata. They were exposed toclinical examination, laboratory investigations (10% KOH and fungal culture), and trichoscope examination. Results. Our obtained results reported that, in tinea capitis patients, comma shaped hairs, corkscrew hairs, and zigzag shaped hairs are the diagnostic trichoscopic features of tinea capitis. While in alopecia areata patients, the most trichoscopic specific features were yellow dots, exclamation mark, and short vellus hairs. Conclusion. Trichoscopy can be used as a noninvasive tool for rapid diagnosis of tinea capitis and alopecia areata in pediatric patients.